ПОТРЕБИТЕЛЬСКОЕ КРЕДИТОВАНИЕ В РОССИИ: ОСНОВНЫЕ ПРОБЛЕМЫ НА СОВРЕМЕННОМ ЭТАПЕ - A. Fedorova; R. Cherkashnev; O. Chernyshova (Вестник Северо-Кавказского федерального университета, 2022)
This article is devoted to the current state and problems of consumer lending in Russian commercial banks. As a result of the research, it was found that during the analyzed period, the volume of consumer lending in Russia increased, reaching the level of 17 475 billion rubles in December 2019. Almost half of the working population of Russia has consumer loans. In January - February 2020, 2.61 million consumer loans were issued. The identified problems in the sphere of consumer lending included: unsecured loans, a decrease in the solvency of the population, a fairly rapid spread of Express lending (from January 2018 to January 2019, the growth in the volume of issued POS loans amounted to 8.8%), high interest rates on consumer loans, and as a result, a high percentage of non-repayment of loans. The share of overdue debt on consumer loans is still quite high, although it has a reduction dynamics. in the 4th quarter of 2019, the decrease in the share of overdue debt on consumer loans is typical for almost all regions. In January 2020, the reduction of consumer loan debt (15.5%) continued.